Configuration interaction study on excited electronic states and radiative lifetimes of SnI including spin-orbit coupling. (May 2022) - Li, Rui; Xu, Linxuan; Guo, Huijie; Liu, Xinpeng; Li, Qinan; Yan, Bing
Highlights: The potential energy curves of SnI are calculated with MRCI+Q method. The spin-orbit coupling effects are taken into account in the calculation. Spectroscopic constants of the Λ-S and Ω states of SnI are evaluated. The predissociation mechanism of 1 4 Σ − state is analyzed. Radiative lifetimes of bound stat es of SnI are determined. Abstract: In this work, the high-level multireference configuration interaction (MRCI) method is used to accurately calculate the electronic structure of SnI. In order to guarantee the computational precision, the Davidson correction (+Q), core-valence (CV) electrons correlations and spin-orbit coupling (SOC) effect are also considered. According to the calculated potential energy curves (PECs) of the Λ-S states and Ω states, the spectroscopic constants of the bound states are estimated. The interaction of crossing states are investigated, and with the aid of calculated SO matrix elements, the predissociation pathways of 1 4 Σ − state are revealed. In addition, the transition dipole moments (TDMs) and Franck-Condon factors (FCFs) from the excited states to the ground state are determined. Finally, the radiative lifetimes of bound states are calculated, and the influences of SOC effect on radiative lifetimes are illuminated. Graphical abstract: Image, graphical abstract